PENERAPAN MODEL PROBLEM-BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SISTEM HUKUM DAN PERADILAN DI INDONESIA Kelas XI - Dwi Budiningtyas, S.H (JARDIKNAS - Jurnal Pendidikan dan Sosial, 2021)
This research concern to improve student learning by class of XI IPS In SMA Negeri 1 Rasau Jaya 2019/2020 on Subject of legal and judicial system by using Problem-Based Model (PBL) in Indonesia. This research concern on classroom action research (CAR). These subjects were from class of xi Ips 1 that have 30 students. This research is taken in 2 cycles that have 2 meeting in each cycle. Each cycle has 4 steps that are strategy, the implementation of act, observation and reflection. First and second cycle discussed main subject of legal and judicial system in Indonesia. The instruments of collecting data used by observation, questionnaire and written test. Beside of that, the writer used the data analysis as a descriptive. The result of this research shows that the implementation Problem-Based Learning Model (PBL) can improve student learning outcomes in class of xi Ips 1. Its start from pre-action, first cycle and second cycle that 40% students passed by implementation steps. After act step that used implementation of Problem-Based Learning model (PBL), then the result of student learning increase to 70% by first cycle and in second cycle become 93,33%. So, with this learning model the number of students got passing grade/ complete score (KKM) in subject of legal and judicial system in Indonesia were 28 students (93,33%). In conclusion, the research of implementation learning Problem-Based Learning model (PBL) can improve student learning outcomes by class of XI IPS 1 that used subject of legal and judicial system in Indonesia